2019
DOI: 10.1259/bjr.20180670
|View full text |Cite
|
Sign up to set email alerts
|

Realizing the potential of magnetic resonance image guided radiotherapy in gynaecological and rectal cancer

Abstract: CT-based radiotherapy workflow is limited by poor soft tissue definition in the pelvis and reliance on rigid registration methods. Current image-guided radiotherapy and adaptive radiotherapy models therefore have limited ability to improve clinical outcomes. The advent of MRI-guided radiotherapy solutions provides the opportunity to overcome these limitations with the potential to deliver online real-time MRI-based plan adaptation on a daily basis, a true “plan of the day.” This review describes the applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 100 publications
0
15
0
Order By: Relevance
“…A limitation of this study is the moderate number of patients [20] and fractions (300) used for analyses. The significance and large difference between the online strategy and plan selection for all dose levels and for both SCRT and LCRT is, however, convincing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A limitation of this study is the moderate number of patients [20] and fractions (300) used for analyses. The significance and large difference between the online strategy and plan selection for all dose levels and for both SCRT and LCRT is, however, convincing.…”
Section: Discussionmentioning
confidence: 99%
“…Recent developments in improved image quality for treatment guidance, such as MRI-guided radiotherapy and CBCT guidance, as well as developments in fast and precise auto-contouring [18] and auto-planning 'marks the beginning of a new era' [19]. Online adaptive treatment, based on both MRI and CBCT guidance, is now a real possibility [19][20][21][22] and surely promising in reducing dose to the OARs even further.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of MRI imaging in cervical cancer management is well established [51]; including its transformation of IGABT. Magnetic resonanceguided radiation therapy (MRgRT) uses superior image quality [54,69] compared to computed tomography (CT), enhancing soft-tissue visibility and reducing inter-observer variability in contour delineation. Studies comparing CTand MRI-guided contour delineation for IGABT have shown that tumour contours can be significantly overestimated on CT [56,70].…”
Section: Magnetic Resonance Imaging-guided Online Adaptive Radiotherapymentioning
confidence: 99%
“…[1][2][3][4][5][6] The potential for real-time adaptive radiotherapy (ART) could help us to achieve more accurate treatment delivery for pelvic sites, which are subject to large and irreproducible inter-and intra-fractional anatomical variations. [5][6][7] Variations in rectal gas have been shown to influence target coverage during conventional cervical, bladder and prostate cancer radiotherapy. [8][9][10][11][12][13] Furthermore, due to the electron return effect (ERE), there is a potential for dose perturbation in the rectal wall during MRIgRT treatment of these sites.…”
Section: Introductionmentioning
confidence: 99%
“…With superior soft tissue contrast to cone-beam computed tomography (CBCT) and the potential for real-time imaging, magnetic resonance imaging guided radiotherapy (MRIgRT) shows promise for pelvic sites including the cervix, bladder and prostate. [1][2][3][4][5][6] The potential for real-time adaptive radiotherapy (ART) could help us to achieve more accurate treatment delivery for pelvic sites, which are subject to large and irreproducible inter-and intra-fractional anatomical variations. [5][6][7] Variations in rectal gas have been shown to influence target coverage during conventional cervical, bladder and prostate cancer radiotherapy.…”
Section: Introductionmentioning
confidence: 99%